Numerical Optimization Method and Experimental Verification of Contact Strength of U-Joint Bearings - Niu Jie; Ye Lianqiang; Dong Xiaozhong; Gao Tianfen; Gu Fuxiang (Jixie chuandong)
Focusing on the insufficient life of a heavy U-joint bearing and taking the contact strength as the key analysis, the influence of the bottom support of the case of the U-joint bearing on the contact strength is analyzed. It is believed that the support effect of the case should be considered in numerical calculation model of the U-joint bearing strength. Through the comparative analysis of multi-group crown and taper optimization under three kinds of needle diameters, it is found that the journal taper is most sensitive to the life of U-joint comparing to the needle crown height and needle crown length. It is also found that under different design parameters, the influence tendency of light load and heavy load on bearing strength is not exactly identical. Hence, it should be analyzed according to the actual load situation. The optimization results show that the contact stress of the needle roller bearing is reduced by 18.4%, the minimum test life of the U-joint bearing is increased by 28.6%, and the maximum test life is increased by 61%, indicating the nonlinear relationship between the life of the U-joint needle roller bearing and the structural parameters, and also show the correctness of the optimization model and analysis scheme of U-joint contact strength. It is significant in providing reference for the life optimization method of U-joint with needle roller crowns and journal tapers.